2018
DOI: 10.1515/jpem-2017-0209
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation of glycogen storage disease types Ia and III in children with short stature and hepatomegaly

Abstract: They highlight the importance of considering glycogen storage disease in a child presenting with short stature, as it is a treatable disease that can be diagnosed non-invasively with genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Several case reports and large cohort studies were reported for GSD III, [20][21][22][23][24][25][26] summarized in Table S1. Large cohorts included patients with ages averaging 26 years, 10 19 years, 12 or 17 years.…”
Section: Review Of Literature For Gsd III Patientsmentioning
confidence: 99%
“…Several case reports and large cohort studies were reported for GSD III, [20][21][22][23][24][25][26] summarized in Table S1. Large cohorts included patients with ages averaging 26 years, 10 19 years, 12 or 17 years.…”
Section: Review Of Literature For Gsd III Patientsmentioning
confidence: 99%
“…The pathophysiology of these endocrine manifestations is not yet well understood, but insulin resistance (due to regular ingestion of glucose and excess body weight) appears to be one of the main factors [ 50 , 51 ].…”
Section: Diagnosis and Initial Assessmentmentioning
confidence: 99%
“…It is relatively rare with an estimated incidence of 1 : 100000 births [2]. GSDIII is a subtype of hepatic glycogen storage disease (GSDs), presenting with hepatomegaly, hepatic dysfunction, hypoglycemia, hyperlipidemia, growth retardation, as well as progressive myopathy and cardiomyopathy [3][4][5][6][7][8]. Tere are four subtypes in GSDIII classifed based on the diference of the tissues involved and variated regions of the GSD enzyme.…”
Section: Introductionmentioning
confidence: 99%